Preliminary Results of Titanium Diffusion on Shinbone of Mice with Osseointegrated Implants - Grenón Miriam; Sanchez Héctor J; Fontana Sebastian; Robledo Jose (2013)
The use of Ti-based dental implants to replace lost dental elements is increasingly frequent. Dental implants are composed of Ti IV-type which is an alloy of titanium, aluminum and vanadium. When the implant is contacted with the tissue, a modification in its surface undergoes, releasing particles of titanium in different concentrations. Titanium is a transition element extremely resistant to corrosion; it is present at trace levels in tissues and body fluids in concentrations not well established. The metabolism of free titanium is not well known. Titanium up-taking mode or movement in the body is not known, nor its toxic dose. This research group has studied the behavior of titanium concentration of dental supra- and infra-gingival calculus at different stages of maturation. The studies involved analyses of saliva and gingival fluid in different local situations, corresponding to healthy and ill subjects, smokers and nonsmokers, postmenopausal women with osteopenia and osteoporosis, patients affected by periodontal disease with and without treatment, people with different calcium intake in the diet, etc.. The results show large variations in the concentration of titanium. Another study measured saliva and gingival fluid of patients with dental implants by TXRF with synchrotron radiation. The mean concentration measured in saliva was 3.5 § 0.5 ppm in patients without implants and 2.8 § 0.5 ppm in patients with implants. In gingival fluid of patients without implants the concentration was 1.3 § 0.4 ppm, while in gingival fluid it was found 22 § 7 ppm. Levels of confidence (ANOVA) between the groups were p > 0.33 for saliva and p < 0.005 for gingival fluid. There is a greater tendency to increase the concentration of titanium in gingival fluid of patients with implants, while there are no significant differences in saliva [1]. The micro-XRF technique is a suitable method for measuring trace elements in small samples whether liquid or solid. After studied the behavior of titanium in oral fluids, we interested to know the titanium behavior in bone tissue. In this work we analyze the titanium diffusion through the shinbone bone of mice.